Evaluation of evolution of myocardial infarction by serial determinations of serum creatine kinase activity. Issue 5 (May 1977) - Inoue, M; Hori, M; Fukui, S; Abe, H; Minamino, T
Abstract : In order to investigate the relation between the release of creatine kinase (CK) in acute myocardial infarction and the evolution of infarction, the appearance functions of CK (release of CK from the heart into the circulation) were calculated by the modified method of Sobel and associates from the serial determinations of serum CK activity in 50 patients with acute myocardial infarction. The relation of the time between the onset of infarction and the peak value of the appearance function to the duration of the evolution of abnormal Q waves in 14 patients with inferior infarction and to the duration of pain in all patients was investigated. The duration of CK release from the heart averaged 37-2+/-2-4 hours and correlated well with the total CK released (R=0.665) which represents the infarct size. The mean per cent of the total CK eventually released by the time of maximum sigmaQ (sum of the amplitude of Q wave in leads II, III, and aVF) was 80-0+/-6-4 per cent and that of CK released while pain persisted was 72-0+/-3-9 per cent. These results strongly suggest that the appearance function of CK reflects the evolution of myocardial infarction.